Application of environmental management accounting by small and medium enterprises in South Africa - Thomas Nyahuna; Mishelle Doorasamy (Environmental Economics, 2021)
By focusing on environmental management accounting in SMEs, the study helps SME managers to effectively understand and find better ways of improving environmental management. The paper investigates environmental management accounting applications in manufacturing small and medium enterprises in Gauteng province. Small and medium enterprises were chosen based on their exclusion from the mainstream research on environmental management accounting (EMA). To achieve the main aim of the study, 24 in-depth interviews were undertaken among SMEs’ managers, accountants, chief executive officers, and owners. The study found that physical EMA is more common in SMEs than monetary EMA. 77% of SMEs’ respondents confirm using physical environmental information in their operations. Therefore, SMEs prefer EMA practices with little cost or no cost attached and practices that can effectively generate returns in the short term. In addition, the avoidance of monetary EMA is anchored on the premise of avoiding costly projects with no immediate material financial returns. Therefore, EMA is critical for SMEs to achieve sustainability.